Assimetria cerebral na discriminação de expressões faciais de baixa intensidade emocional em condições de longa observação: um experimento online - Encide, Lídia Rezende (2021)
Brain asymmetry referring to the recognition of emotional faces has been studied broadly in the last few years. Recently, there are three theories about the emotional processment. The first one, the right hemisphere hypothesis, claims that this hemisphere presents a superiority in production and perception of all emotional facial expressions. The valency hypothesis stands that there is a superiority of the left brain to positive emotions and of the right hemisphere to the negative ones. The modified valency hypothesis defends that the right hemisphere is the one specialized in negative emotions, while both of them process positive emotions. However, part of those researches show contradictory results concerning the hemispheres’ involvement in emotional processing.Objective: In this study, the goal was to evaluate how brain hemispheres compare and identify different facial expressions of low intensity emotions in healthy volunteers. Method: A total of 70 subjects took part in this study. Each participant was submitted to the online experimental task of evaluating facial expressions of joy, disgust, anger and sadness. The faces were shown in pairs, one on the right and the other on the left of the focal point, whilst varying in emotional intensity (by 0, 5, 10 and 15%). After each pair was presented, the participants were asked to indicate the side (left or right) that showed the strongest emotional intensity. Results: The Wilcoxon test indicated that the participants were more correct and had the fastest reaction times when the faces of higher intensity were shown om the right side of the focal point, comparing to the left (p<0,05). The statistical analysis also showed that, in the pairs with the same emotional intensity, there was a tendency of considering the expression of disgust on the right side more intense than the one on the left of the focal point (p=0,004). Conclusion: When analysed together, the results indicate that there is an advantage of the left hemisphere in the discrimination of facial emotions. This study does not offer support to the right hemisphere hypothesis as well as the valency hypothesis and its variations, given the advantage found in the discrimination of anger and sadness in the right visual field (left hemisphere). The study is relevant for it shows the effects of brain asymmetry in the evaluation of facial expressions are shown even in less controlled situations, like an online study, as well as it contributes for the elaboration of more adequate methods in future studies concerning brain asymmetry.